2021
DOI: 10.1108/ics-11-2020-0192
|View full text |Cite
|
Sign up to set email alerts
|

Accessible authentication: dyslexia and password strategies

Abstract: Purpose The purpose of this paper is to reveal the lived experiences of dyslexics in engaging with all kinds of alphanumeric authentication mechanisms. Design/methodology/approach A significant proportion of the world’s population experiences some degree of dyslexia, which can lead to spelling, processing, sequencing and retention difficulties. Passwords, being essentially sequences of alphanumeric characters, make it likely that dyslexics will struggle with these, even more so than the rest of the populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The majority stem from usability issues -such as compatibility problems with assistive technologies (P7), lack of contrast on the smartphone keyboards (P12, P13), non-readable password fields (P1, P10), or solving CAPTCHAs in the enrolment or authentication process (P5, P8, P9) -that have also been identified by other research, e.g., [20], [61]. These also have an effect on security, e.g., similar to people with dyslexia [22], [39], [52], [57] P1, with learning difficulties, finds it hard to create and remember secure passwords, so they reduce the length of the passwords and choose family names or a date of birth as a password to be able to memorize it easily. Such adaptations commonly come at the cost of security, as shown in P1's experience:…”
Section: Lack Of Accessible Authentication Forces Users With Disabili...mentioning
confidence: 87%
See 2 more Smart Citations
“…The majority stem from usability issues -such as compatibility problems with assistive technologies (P7), lack of contrast on the smartphone keyboards (P12, P13), non-readable password fields (P1, P10), or solving CAPTCHAs in the enrolment or authentication process (P5, P8, P9) -that have also been identified by other research, e.g., [20], [61]. These also have an effect on security, e.g., similar to people with dyslexia [22], [39], [52], [57] P1, with learning difficulties, finds it hard to create and remember secure passwords, so they reduce the length of the passwords and choose family names or a date of birth as a password to be able to memorize it easily. Such adaptations commonly come at the cost of security, as shown in P1's experience:…”
Section: Lack Of Accessible Authentication Forces Users With Disabili...mentioning
confidence: 87%
“…Cognitive Impairments. Recently, researchers started to look more closely at the needs of people with cognitive impairments, such as dyslexia [22], [32], [39], [52], [57]. Hayes et al [32], Renaud et al [57], and Ophoff et al [52] found that difficulties occur in entering passwords, memorizing patterns, PINs, tokens, and identifying objects in pictures (CAPTCHAs).…”
Section: Disability and Authenticationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many older adults experience a measure of cognitive decline [ 56 ]. For example, dyslexia impacts at least 10% of the population, and impacts cyber security behaviours [ 54 , 76 ]. Users with other limitations, such as those with Down syndrome, need more time than other users to carry out tasks [ 52 ].…”
Section: Accessibility and Vulnerabilitymentioning
confidence: 99%
“…This option requires the user to read and correctly transfer the number to the device they are logging in on. These codes expire within seconds/minutes so even a slight delay caused by age-related slowness might invalidate them, which will eventually lock the user out of their account [ 76 ]. (2) approval of a login attempt via a 2FA app .…”
Section: Barriers To Accessible Cyber Guidancementioning
confidence: 99%